Effectiveness of an Evidence‐Based Practice Nurse Mentor Training Program. Issue 3 (23rd March 2017) - Spiva, LeeAnna; Hart, Patricia L.; Patrick, Sara; Waggoner, Jessica; Jackson, Charon; Threatt, Jamie L.
ABSTRACT: Background: Multiple reasons are cited for why nurses do not incorporate evidence into clinical practice, including lack of knowledge and skills, training, time, and organizational support. Aims: To investigate the effectiveness of a mentor training program on mentors' perceptions of knowledge, attitude, skill, and confidence levels, and organizational readiness related to evidence‐based practice (EBP) and research utilization; and to investigate the effectiveness of creating a formalized structure to enculturate EBP in order to prepare nurses to incorporate EBP into clinical practice on nurses' perceptions of knowledge, attitude, skill levels, barriers, nursing leadership, and organizational support related to EBP and research utilization. Methods: A two‐group pretest–posttest quasi‐experimental, interventional design was used. A convenience sample of 66 mentors and 367 nurses working at a five hospital integrated healthcare system located in the Southeastern United States participated. Findings: Nurse mentors' knowledge, attitude, skill level, and organizational readiness related to EBP, t = −8.64, p < .001, and confidence, t = −6.36, p < .001, improved after training. Nurses' knowledge, attitude, and skill level related to EBP, t = −19.12, p < .001, and barriers to research utilization, t = 20.86, p < .001, EBP work environment t = −20.18, p < .001, and EBP nurse leadership, t = −16.50, p < .001, improved after a formalized structure was implemented. Linking Evidence to Action: EBP mentors are effective in educating and supporting nurses in evidence‐based care. Leaders should use a multifaceted approach to build and sustain EBP, including developing a critical mass of EBP mentors to work with point of care staff.